STRATEGI PENGEMBANGAN WISATA BIRDWATCHING DI KAWASAN TAMAN WISATA ALAM SIJABA HUTAGINJANG - Joko Mijiarto (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
TWA Sijaba Hutaginjang TWA area has the potential to be developed into a birdwatching tourist destination. For this reason, a birdwatching tourism development strategy is needed in the area. The purpose of the study was to develop a strategy for developing birdwatching tourism in the TWA Sijaba Hutaginjang area. The research was carried out in May 2021 with a literature study of documents related to TWA Sijaba Hutaginjang. Analysis of strategy preparation is carried out using SWOT analysis. In the Sijaba Hutaginjang TWA area, there are 29 species of birds that have the potential to be an attraction in this area. Where 5 bird species are included in protected bird species based on government and international regulations.Keyword: Birdwatching, strategy, TWA Sijaba Hutaginjang, tourism